REFRAMING CURRICULUM DEVELOPMENT IN CONTEMPORARY EDUCATION: INTEGRATING THEORETICAL FOUNDATIONS, DEVELOPMENT MODELS, AND POLICY TRANSFORMATION IN INDONESIA - Ahmad Mahali; Nanang Budianto; Maskur Azka (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
Curriculum is a fundamental component of the educational system that serves as a guideline for the implementation of the teaching and learning process. The development of science, technology, and social dynamics requires curriculum development that is relevant and adaptable to the needs of society. This article aims to examine the basic concepts of curriculum development, the principles underlying it, various curriculum development models, and curriculum development policies in Indonesia. The method used in this study is library research by analyzing various literature sources related to curriculum development. The findings indicate that curriculum development is a systematic process involving the planning of educational objectives, the organization of learning materials, instructional strategies, and learning evaluation. Curriculum development should be based on the principles of relevance, flexibility, continuity, effectiveness, and student-centeredness. Curriculum policies in Indonesia continue to evolve as a form of adaptation to contemporary needs, as reflected in the implementation of the 2013 Curriculum and the Merdeka Curriculum. The Merdeka Curriculum provides greater opportunities for educational institutions to develop learning processes that are aligned with the characteristics of students. Therefore, a comprehensive understanding of curriculum development concepts and policies is essential for educators in improving the quality of education